2021
DOI: 10.21203/rs.3.rs-828936/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proper protein intake, adequate sleep and short screen time can promote physical growth and reduce the incidence of obesity in children aged 3~7 years

Abstract: Background With the rapid development of social economy in China, children's dietary behaviors and lifestyle has undergone great changes. Picking eating, inappropriate protein intake, inactive lifestyle may lead to children's poor physical growth. Especially for preschool children who are in the key period for the formation of dietary habits and lifestyle, early identification of problems in their diet and living habits and interventions will be the key procedure to improve the growth and health level of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Involvement and education of fathers are essential to adhering to family-centered care principles in situations where some pediatrics' hospitals have restricted the presence of family members to reduce transmission of COVID-19 2,34 . Although there was no significant relationship between mothers' perceptions of their children's sleep, but mothers reported improvement in their children's sleep, and mothers reported fewer sleep problems during their children sleeping; however, difficult sleeping was still reported in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Involvement and education of fathers are essential to adhering to family-centered care principles in situations where some pediatrics' hospitals have restricted the presence of family members to reduce transmission of COVID-19 2,34 . Although there was no significant relationship between mothers' perceptions of their children's sleep, but mothers reported improvement in their children's sleep, and mothers reported fewer sleep problems during their children sleeping; however, difficult sleeping was still reported in children.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement and education of fathers are essential to adhering to family-centered care principles in situations where some pediatrics’ hospitals have restricted the presence of family members to reduce transmission of COVID-19 2 , 34 . Therefore, in an online intervention for fathers in the present study, the results showed that the educational-supportive intervention of fathers is beneficial in improving various aspects of sleep in hospitalized infants and toddlers with pneumonia, including daytime sleep, total sleep time, and mothers’ behavior toward children’s sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation